2001
DOI: 10.1067/mtc.2001.110683
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acutely increased left ventricular afterload on work output from the right ventricle in conscious dogs

Abstract: Increased left ventricular afterload decreases global and regional right ventricular stroke work at any given preload, a direct, negative systolic ventricular interaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Complete pericardial closure could not be achieved because it would have interfered with the position of the PA occluder and would have produced an unphysiologically high degree of constriction. 9 After 1 week of recovery from the operation, the cuff was inflated by means of stepwise injection of hypertonic saline into the reservoir over a period of 2 weeks until the right ventricle faced a pressure equal to the systemic (aortic) pressure. During the next 8-week period, RV peak systolic pressure was kept at the level of peak aortic systolic pressure through biweekly monitoring of RV and aortic pressures by using the subcutaneous reservoirs, followed by PA cuff adjustments, if necessary.…”
Section: Pab Operationmentioning
confidence: 99%
“…Complete pericardial closure could not be achieved because it would have interfered with the position of the PA occluder and would have produced an unphysiologically high degree of constriction. 9 After 1 week of recovery from the operation, the cuff was inflated by means of stepwise injection of hypertonic saline into the reservoir over a period of 2 weeks until the right ventricle faced a pressure equal to the systemic (aortic) pressure. During the next 8-week period, RV peak systolic pressure was kept at the level of peak aortic systolic pressure through biweekly monitoring of RV and aortic pressures by using the subcutaneous reservoirs, followed by PA cuff adjustments, if necessary.…”
Section: Pab Operationmentioning
confidence: 99%
“…A study condicted in dogs with normal RV afterload showed that an increase in LV afterload reduces RV contractility. 26 However, others have shown a beneficial effect of LV afterload increase when RV performance is compromised, and in a study conducted with phenylephrine, there was no impact on RV contractility which suggests that an increase in systemic pressure cannot solely explain the potential negative inotropic effect of vasopressin. 24,27…”
Section: Considerations For Use In Pahmentioning
confidence: 97%
“…1 Diastolic ventricular interdependence is well recognized; however, systolic ventricular interdependence mediated by the myocardium is less widely appreciated. [1][2][3][4][5][6] Systolic ventricular interdependence has been attributed primarily to the interventricular septum and may have important hemodynamic implications. 4,7,8 Systolic ventricular interdependence is believed to be an important mediator in the hemodynamic response to right ventricular (RV) pressure or volume overload and may explain RV failure following cardiac surgery, cardiac transplantation, and left ventricular (LV) assist device placement.…”
Section: Original Research Pulmonary Vascular Diseasementioning
confidence: 99%